Using a co-created checklist to improve on-farm biosecurity: an observational pilot intervention with pig farmers and livestock field officers in Sumbawanga, Tanzania - Auplish, Aashima; Mjuberi, Kuboja; Magwisha, Henry; Tago, Damian; Buckel, Anica; Ciamarra, Ugo Pica; Mclaws, Melissa; Heilmann, Martin (Frontiers in Veterinary Science, 2025)
The Tanzanian pig sector has the capacity to become market-oriented but it is constrained by significant factors like poor husbandry, management practices and disease, like African swine fever (ASF). Good biosecurity is essential to prevent, minimise or even eliminate biosecurity risks on farms. This study aimed to evaluate a pilot intervention based on an innovative, participatory approach to progressively improve biosecurity practices on small- and medium-scale pig farms in Tanzania. An observational study was conducted, where 30 farms were systematically monitored to assess the impact of using a co-created checklist on biosecurity compliance and production parameters. Livestock field officers (LFOs) were trained to provide technical guidance to farmers to implement the checklist. Focus group discussions (FGDs) were also conducted with LFOs, which were coded and thematically analysed. The median compliance score for biosecurity was significantly higher after the pilot intervention (20.0 out of 26 practices or 76.9%) compared to baseline (median of 5.50 out of 26 practices 21.2%). The time spent implementing biosecurity per sow (per day) increased from a median of 7.8–18.6 min by the end of the intervention. Pre-weaning mortality decreased from 28.6 to 25.0% and cost of antimicrobial use per sow (per month) was reduced by 57%. Meanwhile, FGDs revealed that the pilot intervention allowed LFOs to connect with farmers to provide services and collaborate with other LFOs to co-develop solutions for farmers. Despite an initial lack of trust, the relationships between LFOs and farmers were described to have positively transformed. These findings highlight the potential of using bottom-up approaches, combined with sensitisation and capacity-building, to address the unique challenges of biosecurity in low-resource settings.